Emerging tobacco use patterns in the United States: Tobacco use behaviors associated with current use of nicotine pouches - Julia N. Soulakova; Lisa J. Crockett (PLoS ONE, 2026)
Nicotine pouches (NPs) are non-combustible tobacco products marketed as alternatives to traditional tobacco. Recent studies suggest an increasing use of NPs in the United States. The primary goals of this study were to assess the associations between current use of each of the seven other tobacco products and current use of NPs among U.S. adults (18+), and to determine which other products are significantly associated with current use of NPs. The secondary goals were to describe the population of adults who currently use NPs in terms of their tobacco use behaviors and sociodemographic characteristics. Data from the 2022–2023 Tobacco Use Supplement (TUS) to the Current Population Survey (CPS), collected in the U.S., were used in this cross-sectional study to address the primary (n = 107,281) and secondary (n = 537) goals. The primary outcome was current NP use (yes/no). All analyses accounted for the TUS-CPS complex design. The prevalence of current NP use was 0.47% (SE = 0.03%), corresponding to an estimated 1,146,681 adults nationwide. Adults who currently used smokeless tobacco (aOR=12.03, 95% CI = 8.83-16.39) had the highest odds of current use of NPs, followed by those who used heated tobacco (aOR=4.84, 95% CI = 2.01-11.67), hookah tobacco (aOR=3.70, 95%CI = 1.55-8.82), e-cigarettes (aOR=2.90, 95% CI = 1.84-4.60), cigars (aOR=2.48, 95% CI = 1.71-3.58), and combustible cigarettes (aOR=1.84, 95% CI = 1.38-2.45). Among adults who currently use NPs, 61.00% (SE = 2.59%) used at least one other tobacco product and the most commonly used products were smokeless tobacco (27.39%), combustible cigarettes (21.74%), e-cigarettes (20.54%), and cigars (17.30%). The observed sociodemographic profile of adults who use NPs (e.g., 89.14% are men) suggests that NPs may be reaching subgroups that differ from those who typically use other tobacco products. The findings underscore the need for further research to determine whether use of NPs leads to product switching, cessation, or sustained poly-tobacco use.